Titanite Mineralization of Microbial Bioalteration Textures in Jurassic Volcanic Glass, Coast Range Ophiolite, California - Izawa, Matthew R. M.; Banerjee, Neil R.; Shervais, John W.; Flemming, Roberta L.; Hetherington, Callum J.; Muehlenbachs, Karlis; Schultz, Cynthia; Das, Debarati; Hanan, Barry B. (Frontiers in Earth Science, 2019)
Volcanic glasses are rarely preserved in the rock record, and the quality of preservation generally declines with increasing age. Records preserved in ancient basaltic glasses therefore provide important links between processes operating in the distant past, and those that are active on the Earth today. Microbial colonization has been linked to the formation of characteristic structures in basaltic glass, including tubules and granule-filled tubules, which are thought to be produced by microbially-mediated glass dissolution. Structures of similar occurrence and morphology but filled almost entirely with fine-grained titanite have been documented in some ancient metabasalts. It has been suggested that the ancient titanite-mineralized structures are mineralized equivalents of hollow tubules in modern glassy basaltic rocks, but a direct link has not been firmly established. We report the discovery of tubular bioalteration structures in fresh and minimally-altered basaltic glasses of middle Jurassic (164 Ma) age from the Stonyford Volcanic Complex (SFVC), Coast Range Ophiolite, California. Tubular structures hosted in unaltered basaltic glass are typically hollow, whilst those in zones of zeolitic alteration are mineralized by titanite. Tubules are continuous across zeolite-glass interfaces, which mark an abrupt change from titanite-filled to hollow tubules, demonstrating that titanite growth occurs preferentially within pre-existing tubular structures. Titanite mineralization in the Stonyford Volcanic Complex represent a link between tubular structures in modern basaltic glass and titanite-mineralized features of similar morphology and spatial distribution in ancient metabasalts. Our observations support a link between textures in modern glassy basaltic rocks and some of the oldest-known putative ichnofossils.